Fifty beasts to break your heart : & other stories - Nethercott, GennaRose (Vintage Books, a division of Penguin Random House LLC, 2024)
"From the author of the breakout fantasy novel Thistlefoot: a collection of dark fairytales and fractured folklore exploring all the ways love can save us-or go monstrously wrong. The stories in Fifty Beasts to Break Your Heart are about the abomination that resides within us all. That churning, clawing, hungry yearning: the desire to be loved, and seen, and known. And the terror of those things too: to be loved too well, or not enough, or for long enough. To be laid bare before your sweetheart, to their horror. To be known and recognized as the monstrous thing you are. Two young women working at a sinister roadside attraction called the Eternal Staircase explore its secrets-and their own doomed summer love. A group of witchy teens concoct the perfect plan to induce the hated new girl into their ranks. A woman moves into a new house with her acclaimed artist boyfriend and finds her body slowly shifting into something specially constructed to accommodate his needs and whims. And two outcasts, a vampire and a goat woman, find solace in each other, even as the world's lack of understanding might bring about its own end. In these lush, beautifully written stories, GennaRose Nethercott explores love in all its diamond-dark facets to create a collection that will redefine what you see as a beast, and make you beg to have your heart broken."--